Neuroscience and the teaching of mathematics: a study on learning styles and multiple (Research, Society and Development, 2019)
This article presents an analysis of neuroscience as a significant driver in the mathematics teachers' guideline and in the study of their teaching practice in which the teaching-learning process is reflected. The aim of the research is to investigate the relationship between Learning Styles and Multiple Intelligences Theory in mathematics teaching. As a research methodology to elucidate these questions, the bibliographic research was adopted. From the analysis of the present study, it is concluded that the existence of an inclusive relationship makes the learning styles and the multiple intelligences of the students relate to each other. However, brain study for math classes will bring many benefits to teachers, which will facilitate student performance.